The Effctiveness of Using Animaker-based Animation Media trough the Problem Based Learning Model on the Civic Education Learning Outcomes of Elementary School Students - Tasqia Shabrina; Nurul Hidayah; Anton Tri Hasnanto (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
This study aims to examine the effect of using Animaker-based animation media integrated with the Problem-Based Learning (PBL) model on the Civic Education (PKn) learning outcomes of fourth-grade students at SD Al-Azhar 2 Bandar Lampung. This research employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The students were divided into two groups: an experimental group that received instruction using Animaker media within the PBL framework, and a control group that was taught using conventional PowerPoint presentations. Data were collected through pre-tests and post-tests and analyzed using Welch’s t-test because the data were normally distributed but exhibited heterogeneity of variance. The results showed a significant difference between the two groups (Sig. 2-tailed < 0.001), with the experimental group achieving a mean post-test score of 84.30 compared with 70.90 in the control group, indicating a difference of 13.40 points. These findings suggest that integrating Animaker media with the PBL model significantly enhances students’ Civic Education learning outcomes. Animaker supports comprehension by visualizing abstract concepts, whereas PBL strengthens students’ critical thinking and problem-solving abilities. Thus, the combination of Animaker and PBL can be considered an effective alternative instructional media and learning model.